Indications, Complications, and Retrievals of Inferior Vena Cava Filters in a Colombian Hospital - Juan Carlos Arrieta-Bechara; Daniel A. Jaramillo-Calle; Viviana Andrea Yepes-Gallego; Keiner Toro; Samir Franco-García; Isabel C. Arango M.; Daniel A Jaramillo Calle (Iatreia, 2023)
Introduction: Inferior vena cava filters are endovascular devices utilized in clinical practice to mitigate the risk of acute venous thromboembolic disease progression to pulmonary embolism in cases of absolute contraindications to anticoagulation. Currently, there are no reports on the experience of using such devices in Colombia. Objective: To assess the indications, practices, retrieval rates, and complications of inferior vena cava filters in a university hospital in Colombia. Methods: A retrospective study was conducted at a tertiary-level university hospital in Colombia. Patients who had undergone inferior vena cava filter implantation were included, with exclusion of those with essential data missing for analysis. Descriptive statistics and Student’s t-test were performed for group comparisons. Results: A total of 196 patients with acute venous thromboembolic disease who had undergone inferior vena cava filter implantation were included. None of the patients received the device as primary prophylaxis. Filter-related complications occurred in 13 patients, and retrieval was considered for 118 patients, of whom 108 retrievals were successful. Among the included oncology patients who received an inferior vena cava filter, 36 underwent retrieval attempts, achieving success in 32 cases (88.8%). Conclusions: This study revealed that the most common indications for inferior vena cava filter implantation were the need for surgery, acute bleeding or bleeding risk, and catheter-guided local thrombolysis. The most frequent complication was acute inferior vena cava thrombosis and filter tilting. Inferior vena cava filter retrieval was successful in the majority of attempted cases.